Perspectives on poverty : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Policy at Massey University, Albany, Auckland, New Zealand - Bourke, Sheryl Rose (Massey University, 2013)
The idea that there is poverty experienced in countries that have an abundance of natural resources and accumulated wealth has attracted much public discussion in recent times. This thesis examines the perspectives on poverty of thirty-seven people living in New Zealand communities and situates these perspectives in a wider academic and public discussion. By examining these perspectives a gap in the research on poverty is addressed by taking into account the views and opinions of New Zealanders and relating these perspectives to broader governing processes. The main research strategy is a discourse analysis of thirty seven semi-structured participant interviews. The time period covered in the review of New Zealand literature and public discussion on poverty is from 1972 to the time of the commencement of the interviews in 2008. By employing a Foucauldian theoretical framework drawing on governmentality, the findings from the discourse analysis of thirty-seven participant interviews are explicated and situated within wider social and governing practices. This study highlights a general level of social distancing and “othering” directed at situations described as poverty and how social welfare beneficiaries become the main target for people’s concerns about poverty. Of key interest was the tendency of the participants to spontaneously racialise and define poverty using non-material terminology. As this thesis looks at the implications of a governmentality involved in the development of a self-managing population, it draws attention to the processes of responsibilisation in place for those defined as “poor” in the context of social welfare provision.
Keywords: Poverty; Public opinion; New Zealand